The Disciplinary Committee and the Ethics Committee: main judicial bodies of FIFA = Główne organy sądownicze FIFA: Komitet Dyscyplinrany i Komitet ds. Etyki - Paweł Szwajdler (Kazimierz Wielki University, 2015)
Szwajdler Paweł. The Disciplinary Committee and the Ethics Committee: main judicial bodies of FIFA = Główne organy sądownicze FIFA: Komitet Dyscyplinrany i Komitet ds. Etyki. Journal of Education, Health and Sport. 2015;5(5):510-515. ISSN 2391-8306. DOI 10.5281/zenodo.29043 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A510-515 https://pbn.nauka.gov.pl/works/611690 http://dx.doi.org/10.5281/zenodo.29043 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.05.2015. Revised 28.05.2015. Accepted: 31.05.2015.   The Disciplinary Committee and the Ethics Committee: main judicial bodies of FIFA Główne organy sądownicze FIFA: Komitet Dyscyplinrany i Komitet ds. Etyki   Paweł Szwajdler   Nicolaus Copernicus University in Toruń     E-mail: szwajdli@onet.eu     Abstract        The main purpose of this work is to describe the Disciplinary Committee and the Ethics Committee, which are main judicial bodies of FIFA. The author focuses on differences between these bodies and shows, that both of them was created so as to protect fair play rules. Important part of this work deals with crossing over and doubling up powers of judicial bodies of FIFA and courts of general jurisdiction. Furthermore, the answer to the question: ,,is existence of two first- instance judicial bodies practical?", is in conclusion of this work. The author also focuses on diversity of sanctions applicable to legal and natural persons. In this work, the author analyses legal regulations and specialist literature.   Key words: FIFA, the Ethics Committee, the Disciplinary Committee.